Why is income inequality increasing in the developed world? - Max Roser; Jesus Crespo Cuaresma (Wiley, 2014)
We address empirically the factors affecting the dynamics of income inequality among industrialized economies. Using a panel for 32 developed countries spanning the last four decades, our results indicate that the predictions of the Stolper–Samuelson theorem concerning the effects of international trade on income inequality find support in the data if we concentrate on imports from developing countries as a trade measure, as theory would imply. We find that democratization, the interaction of technology and education, and changes in the relative power of labor unions affect inequality dynamics robustly.